2016
DOI: 10.1007/s40145-016-0184-2
|View full text |Cite
|
Sign up to set email alerts
|

An abnormal displacement change during holding period in nanoindentation tests on zirconia dental ceramic

Abstract: An abnormal displacement change observed during the holding period in nanoindentation tests on a zirconia dental ceramic was reported in this paper. It was found that, at the initial stage of the holding period, the measured displacement versus time curves were similar in shape with the typical indentation creep curve reported in previous studies. As the holding lasted for long time, however, an evident reduction in displacement was observed for tests with high loading rate, implying that another unknown proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…[7] Such analysis is very easy for elastic-plastic material but for materials having time-dependent behavior, this technique becomes delicate as models for mechanical characterization of such materials are not well developed. [8] The load is applied on the sample through the indenter for a particular period of time and the resultant indentation size is measured as in a conventional normal indentation test. The contact compliance method has been recently used for hardness and modulus computation; this method is based on the imposed displacement/reaction force response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Such analysis is very easy for elastic-plastic material but for materials having time-dependent behavior, this technique becomes delicate as models for mechanical characterization of such materials are not well developed. [8] The load is applied on the sample through the indenter for a particular period of time and the resultant indentation size is measured as in a conventional normal indentation test. The contact compliance method has been recently used for hardness and modulus computation; this method is based on the imposed displacement/reaction force response.…”
Section: Introductionmentioning
confidence: 99%
“…YC Lin [7] investigated the effect of different holding times on the nano-mechanical properties of ductile and brittle materials. Zhang et al [8] studied the effect of holding time in nano-indentation tests on zirconia dental ceramic. Chudoba et al [20] worked on different substrates (steel, nickel, glass) and film combinations (diamond-like carbon, Al 2 O 3 , aluminum, gold) to study creep effects on modulus and hardness.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this experiment, the thickness of the Y‐TZP test piece was selected to be 1 mm. Studies have shown that the thickness of a porcelain layer of 1 mm has a transmittance of about 40%, 27,28 so this thickness is also the conventional thickness of ceramic materials for transmission.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in this experiment, the thickness of the Y-TZP test piece was selected to be 1 mm. Studies have shown that the thickness of a porcelain layer of 1 mm has a transmittance of about 40% [24,25], so this thickness is also the conventional thickness of ceramic materials for transmission.…”
Section: Effect Of Colorants On Transmittance Of Y-tzpmentioning
confidence: 99%